(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Over the past 2 decades, the information technology infrastructure has gone through an exponential change with the introduction and evolution of new technologies and trends. Organizations previously having their data on-premise and their infrastructure comprising of multiple server machines on multiple server racks and dedicated client personal computers (PCs) are moving towards cloud computing & virtualization to Smartphone and tablets. This rapid advancement and constant change, although increasing productivity for the organizations is resulting in a rising number of challenges and security issues for the organizations, their managers, IT administrators and technology architects. This paper discusses the future IT infrastructure components and the challenges & security issues that arise after their implementation that needs to be taken care of in order to get the full advantage of IT.